2012
DOI: 10.1039/c2ce06538j
|View full text |Cite
|
Sign up to set email alerts
|

Structural isomerism of an anionic nanoporous In-MOF with interpenetrated diamond-like topology

Abstract: Topologically interesting new In-MOFs were prepared by using a 4,4 0 -biphenyldicarboxylate bridging ligand and In(NO 3 ) 3 $xH 2 O. Two isomeric forms of In-MOFs were independently prepared and characterized by X-ray crystallography, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), elemental analysis, and gas sorption analysis. By simply using different solvents, N,Ndimethylformamide or N,N-diethylformamide, we obtained two new In-MOFs. Despite the same coordination mode of an In III node, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Multicarboxylic acids, especially dicarboxylic acid, have been extensively used to construct metal‐organic frameworks. Benzenedicarboxylic acid, 2, 6‐naphthalene‐dicarboxylic acid and 4, 4′‐diphenyldicarboxylic acid have been successfully introduced in the construction of complexes with novel topologies and multiple functions,2428 which can be assigned to their conformation rigidity and versatile coordination modes. 3‐(4‐Carboxyphenyl) propionic acid (H 2 cpp) has two asymmetric carboxylate groups, in which the longer carboxylate group –CH 2 CH 2 COOH is flexible and able to bend.…”
Section: Introductionmentioning
confidence: 99%
“…Multicarboxylic acids, especially dicarboxylic acid, have been extensively used to construct metal‐organic frameworks. Benzenedicarboxylic acid, 2, 6‐naphthalene‐dicarboxylic acid and 4, 4′‐diphenyldicarboxylic acid have been successfully introduced in the construction of complexes with novel topologies and multiple functions,2428 which can be assigned to their conformation rigidity and versatile coordination modes. 3‐(4‐Carboxyphenyl) propionic acid (H 2 cpp) has two asymmetric carboxylate groups, in which the longer carboxylate group –CH 2 CH 2 COOH is flexible and able to bend.…”
Section: Introductionmentioning
confidence: 99%
“…Both Me 2 NH + 2 and Et 2 NH + 2 directly derived from DMF or DEF solvents may not be suitable for the generation of stable framework structures. Me 2 NH + 2 and Et 2 NH + 2 ions are thought to be generated by thermal decomposition of DMF or DEF, respectively (Gu et al, 2012). Contrarily, as tetraethylammonium bromide (TEAB) was added into the reaction mixture of DEF, good red block crystals were obtained as shown in Figure 2c.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…Additionally, there should be a counter-cation near each [In(O 2 CR) 4 ] − node because of charge matching. There are many examples of 3D In-MOFs solely derived from ditopic, tritopic, tetratopic, and pentatopic carboxylate-based bridging ligands (Sun et al, 2002;Lin et al, 2007Lin et al, , 2012Huh et al, 2009;Gu et al, 2012;Yu et al, 2012;Zheng et al, 2013;Cho et al, 2014;Huang et al, 2014;Johnson et al, 2014;Wang et al, 2014;Grigoropoulos et al, 2016;Li et al, 2016;Aguirre-Díaz et al, 2017;Zhao et al, 2017;Yang et al, 2019). The most common counter-cations are either Me 2 NH + 2 or Et 2 NH + 2 which can be in-situ generated from the solvents: N,Ndimethylformamide (DMF) or N,N-diethylformamide (DEF).…”
Section: Introductionmentioning
confidence: 99%
“…Such difference is explained by the fact that in the case of the two-chain DNA intercalation of the dye occurs between the nucleic bases, preventing the formation of aggregates, whereas the AO in the complexes with RNA is in an aggregated state. Recently it was also shown that the sorption of AO can be used to determine the sorption characteristics of porous CPs [21][22][23][24], although a detailed study of the luminescent characteristics of the obtained materials has not been undertaken.…”
mentioning
confidence: 98%